EVALUASI KINERJA DOSEN OLEH MAHASISWA: ANALISIS PERSEPSI MAHASISWA TERHADAP MUTU PEMBELAJARAN DI PROGRAM STUDI MANAJEMEN PERTANIAN LAHAN KERING - Esra Rombeallo; Deborah Tirtania Chrisna Seko; Risky Meyranti; Reny Wulandari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Student Evaluation of Teaching (SET) is a fundamental internal quality assurance instrument in higher education systems. This study aims to: (1) analyze student perceptions of lecturer performance at the Dryland Agricultural Management (MPLK) Study Program, Politeknik Pertanian Negeri Kupang for the 2025/2026 academic period, based on 22 performance indicators; (2) identify strength dimensions and areas requiring improvement; and (3) formulate data-driven strategic recommendations for sustainable learning quality development. Data were collected through an online Likert-scale questionnaire (1-5) covering five dimensions: discipline, pedagogical competence, communication skills, technology utilization, and fairness in assessment. A total of 55 student respondents evaluated 14 lecturers. Descriptive analysis results show a grand mean of 4.74 (Very Good category), with 13 lecturers (92.9%) rated Very Good and 1 lecturer (7.1%) rated Good. The highest-rated indicators were teaching methods and ability to provide relevant examples (4.84), while the relatively lower indicators were schedule adherence (4.58) and educational technology utilization (4.65). These findings confirm that the study program maintains high and consistent pedagogical standards, yet requires further development in digital literacy and schedule discipline management. Recommendations include organizing regular digital competency workshops, establishing structured schedule communication mechanisms, developing peer learning programs based on best practices, and consistently implementing SET as an integral part of the quality assurance cycle.